Asia's Deepening Regionalism Brings Shared Prosperity - Nag, Rajat M. (2012)
Asia's coming of age has been the development story of the past 40 years. The reasons for this are varied. But some of the more significant factors have been knowledge exchange, technology transfer, and increased economic integration and cooperation between governments of developing economies. Asias success is in part the result of increased dialogue between regional partners, formalized through institutions such as the Association of Southeast Asian Nations (ASEAN), which expanded fromits original five-member core in 1967 to encompass all Southeast Asia by mid-1999 and aims to establish an ASEAN Economic Community by 2015.